2 Answers | Add Yours
The equation to be solved is x^2 = 3x + 5
x^2 = 3x + 5
=> x^2 - 3x - 5 = 0
`x1 = (3 + sqrt (9 + 20))/2`
=> `3/2 + sqrt 29`
`x2 = 3/2 - sqrt 29`
The roots of the equation x^2 = 3x + 5 are `1.5 + sqrt 29` and `1.5 - sqrt 29`
First take all the numbers to one side so u get a equation like this :-
Then go on solving.But how??????
Remeber these two equations so when you get questions like this its easy to solve, the equation is:-
(-b-sqrt(b^2-4ac))/2a and -b+sqrt(b^2-4ac))/2a
then go on subtituting the values as :- a=1 (when no value is in front of x itz always 1)
Then go on suibstituing the values for both the equationns. u will end up getting two answers as :- X= 4.2 (1dp)
these two will be your final answer.
We’ve answered 317,824 questions. We can answer yours, too.Ask a question